Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s13047-020-00393-0
|View full text |Cite
|
Sign up to set email alerts
|

Organizational changes in diabetic foot care practices for patients at low and moderate risk after implementing a comprehensive foot care program in Alberta, Canada

Abstract: Background Neuropathy and vasculopathy can lead to costly and debilitating complications in people with diabetes. The purpose of this study was to evaluate, at an organizational level, uptake of practices included in a diabetic foot care clinical pathway and associated resources. This research focused on patients at low and moderate risk in Alberta, Canada between 2014 to 2019. Methods Serial surveys (2014, 2019) of practices related to screening and care of the feet of people with diabetes. Surveys were admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Early access to outpatient care like high‐risk foot clinics 20 may reduce late, complex presentations of CLTI and facilitate integrated care. Multidisciplinary team (MDT) management reduces amputation rates and improves CLTI outcomes 21,22 through better management of comorbidities and vascular disease 17,23 . Our study highlights that patients aged 75 years or older have poor AFS, increased reoperations and more adverse perioperative outcomes than younger patients.…”
Section: Discussionmentioning
confidence: 81%
“…Early access to outpatient care like high‐risk foot clinics 20 may reduce late, complex presentations of CLTI and facilitate integrated care. Multidisciplinary team (MDT) management reduces amputation rates and improves CLTI outcomes 21,22 through better management of comorbidities and vascular disease 17,23 . Our study highlights that patients aged 75 years or older have poor AFS, increased reoperations and more adverse perioperative outcomes than younger patients.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the guidelines must be as specific as possible to reduce ambiguity and confusion among clinicians managing patients with DFUs [40]. Several studies have shown that developing a national diabetic foot assessment guideline, based on the international recommendations, not only increases the frequency of diabetic foot assessments [42, 43] but also reduces the incidence of diabetes‐related LEA [19, 44]. However, in Belgium, the international recommendations have not yet been implemented into a national diabetic foot assessment guideline.…”
Section: Discussionmentioning
confidence: 99%
“…From an organizational perspective, policy that supports prevention can be developed and led at the provincial level [in Canada]. For example, health leaders in Alberta 12,13 emphasized the need for organizational changes to be led through the implementation of a comprehensive foot care program. 10,11 In the province of Nova Scotia it was reported that, upon implementation of a diabetes-related foot pathway, screening increased significantly and follow up intervals improved.…”
Section: Discussionmentioning
confidence: 99%